Top-k Spatial Keyword Preference Query - Dias de Almeida, João Paulo; Rocha-Junior, João B. (Journal of Information and Data Management, 2016)
With the popularity of devices that are able to annotate data with spatial information (latitude and longitude), more and more spatial data are becoming available. This has attracted the attention from the research community in the processing of advanced spatial queries. In this article, we study a new query type named Top-k Spatial Keyword Preference Query that selects objects of interest based on the textual relevance of other spatio-textual objects in their spatial neighborhood. This article introduces this new query type, presents three algorithms for processing the query efficiently and goes over an extensive experimental evaluation to study the performance of the algorithms proposed, employing real datasets.